INTERGENOMIC CHROMOSOME PAIRING IN ALLOHAPLOID HYBRIDS OF GENUS SOLANUM - T. A. Gavrilenko; G. I. Pendinen; V.-M. Rokka; O. Y. Antonova; R. Thieme (Вавиловский журнал генетики и селекции)
Intergenomic chromosome pairing was analyzed in unique allohaploid hybrids, which had been produced through a process of somatic hybridization followed by a haploidization procedure (in vitro androgenesis). Two hybrid combinations were studied: (1) between cultivated potato S. tuberosum (dihaploid, 2n = 2x = 24, AA genome) and wild species S. etuberosum (2n = 2x = 24, EE genome), (2) between cultivated tomato S. lycopersicum (LL, 2n = 2x = 24) and wild species S. etuberosum (2n = 2x = 24, EE). Genome and chromosome composition of allohaploids were identified through FISH with chromosome specific BAC clones and GISH. Up to 7 intergenomic bivalents per cell were observed in allohaploids between S. tuberosum and S. etuberosum (AE); the chiasmata were distributed in the distal regions of long arms of each chromosome and in the short arms of chromosomes 3, 6, 11, 12. Rare bivalents (from 0 to 2) were observed in allohaploids between S. lycopersicum and S. etuberosum (LE); the chiasmata were distributed in the long arms of chromosome 4 and 6. The perspectives of proposed approach are discussed for application of somatic hybridization and chromosome engineering to study the potential of homeologous pairing and the strategy of introgression.